Ionized gas kinematics and luminosity profiles of Low-z Lyman Alpha Blobs. Issue Volume 15:Issue S359(2020) (March 2019) - Agüero, María P.; Díaz, Rubén; Schirmer, Mischa
Abstract: This work is focused on the characterization of the Seyfert-2 galaxies hosting very large, ultra-luminous narrow-line regions (NLRs) at redshifts z = 0.2−0.34. With a space density of 4.4 Gcp −3 at z ∼ 0.3, these "Low Redshift Lyman-α Blob" (LAB) host galaxies are amongst the rarest objects in the universe, and represent an exceptional and short-lived phenomenon in the life cycle of active galactic nuclei (AGNs). We present the study of GMOS spectra for 13 LAB galaxies covering the rest frame spectral range 3700–6700 Å. Predominantly, the [OIII]λ5007 emission line radial distribution is as widespread as that of the continuum one. The emission line profiles exhibit FWHM between 300–700 Km s −1 . In 7 of 13 cases a broad kinematical component is detected with FWHM within the range 600–1100 Km s −1 . The exceptionally high [OIII]λ5007 luminosity is responsible for very high equivalent width reaching 1500 Å at the nucleus.